ҚАРАҚАЛПАҚСТАН СҮЎРЕТЛЕЎ ӨНЕРИ ЖӘРДЕМИНДЕ ТАЛАБАЛАРДЫҢ КӨРКЕМ ДӨРЕТИЎШИЛИК УҚЫПЛЫЛЫҚЛАРЫН РАЎАЖЛАНДЫРЫЎДЫҢ ПЕДАГОГИКАЛЫҚ ТИЙКАРЛАРЫ - Уразимова, Т.В. (FAN va JAMIYAT, 2021)
The article is dedicated to modern contents of spiritual-creative adding to personalities. Since attention increased in modern society to problem of the shaping all-round developed, spiritual rich and creative to personalities. The Personality of the person, his spiritual and moral look are formed, first of all, in process of the education. So process of the formation necessary to found on making the conditions for unbringing the creative personality ready to dialogue, cooperation and creative activity in different sphere of the lifes.